ANALISIS KRITIK SOSIAL PADA FILM THAGHUT KARYA BOBBY PRASETYO (KAJIAN SOSIOLOGI SASTRA) - Anugrah, Aldi; Idris; Muhammad Idris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research delves deeply into the social critique contained within the film THAGHUT by Bobby Prasetyo, utilizing the perspective of the sociology of literature. This film was selected because it explicitly and implicitly presents various social phenomena that reflect the reality of life in Indonesian society, especially those related to issues of injustice, abuse of power, and community resistance to an oppressive system. This study employs a descriptive qualitative method with content analysis techniques, where the main data is obtained from dialogue, narration, scenes, and visual symbols found within the film.Through the study of the sociology of literature, this research finds that THAGHUT functions not only as a medium of entertainment but also as an effective medium for social critique. The social critique in this film is manifested through the portrayal of characters experiencing oppression, conflicts between the community and those in power, and the use of symbols representing resistance to injustice and authoritarian power. Additionally, the film displays complex social dynamics such as marginalization, discrimination, and the collective struggle of the community to obtain justice.